Obtenção do álcool etílico hidratado, com graduação alcoólica para uso automotivo: validação de um processo em batelada - Michel Junior, Raul José dos Santos (2010)
One of the most used for separation of alcohol and water is distillation. Traditionally the production of hydrated ethanol fuel is produced by large distilleries, which were freestanding or attached. A problem found for production of ethyl alcohol in small properties is related to the type of equipment used and the breaking of the paradigm of food production with energy production in case the fuel. Usually the equipment for small scale production process both in batch or continuous processes by the system relate to the low quality of ethyl alcohol, since most equipment does not provide quality were considered low income, made by hand. A key question for this system is no interference of the production system for joint production of food perfectly integrated into the system. Thus, this study proposes to validate statistically the equipment designed for obtaining alcohol fuel under discontinuous (batch) for small scale production, to evaluate the alcohol obtained is within the regulatory standards of ANP on the alcohol content. To validate the system software was used for specific simulation models also using the Response Surface Methodology, verifying that it is possible to obtain ethanol-grade and quantity for the producer of family farming cooperatives, so that works.